Histopathology of Helicobacter pylori in Chronic Dyspepsia Patients - Wildan Nur; Paulus Kusnanto; Triyanta Yuli Pramana; Michael Tantoro Harnomo; Oyong Oyong; Ambar Mudigdo (The Indonesian Society for Digestive Endoscopy, 2012)
ABSTRACTBackground: Helicobacter pylori (H. pylori) are the most common infection found in dyspepsia cases. This infection is almost always found in digestive tract inflammation and commonly develops into chronic gastritis. Meanwhile, chronic gastritis is a condition assumed as the early event in pathological abnormalities of the stomach which finally may develop into carcinoma of the gaster. In Indonesia, data describing the incidence of H. pylori infection based on the histopathological appearance, location of specimen collection, inflammatory degree, and age of chronic dyspepsia patients is not yet available. The aim of this study is to determine the incidence of H. pylori based on histopathology appearance in chronic dyspepsia patients in Moewardi Hospital Surakarta.Method: This study is a cross sectional descriptive study by performing endoscopy-biopsy and histopathology examination to chronic dyspepsia patients who came to Gastroenterohepatology Clinic, Department of Internal Medicine, Moewardi Hospital, Surakarta on 1 January 2009 - 31 December 2010.Results: More than 90% subjects were 40 year old with the distribution of majority patients were 46-55 year old (32.43%). The most commonly found endoscopic appearance in subjects with positive H. pylori was superficial chronic gastritis (81.08%) with mild inflammatory degree (64.86%) and majority located in the antrum 97.3%.Conclusion: The proporsion of H. pylori infection in male and female was almost equal and was mostly found in the age group of 46-55 year old. This infection frequently happens in chronic dyspepsia who has histopathologic appearance of superficial chronic gastritis with mild inflammatory degree in the antrum area. Keywords: Helicobacter pylori, superficial chronic gastritis, age